Color Choice Preference in Cognitively Impaired Patients: A Look Inside Alzheimer’s Disease Through the Use of Lüscher Color Diagnostic - Stanzani Maserati, Michelangelo; Mitolo, Micaela; Medici, Federica; D’Onofrio, Renato; Oppi, Federico; Poda, Roberto; De Matteis, Maddalena; Tonon, Caterina; Lodi, Raffaele; Liguori, Rocco; Capellari, Sabina (Frontiers in Psychology, 2019)
Objective To study the emotional state of cognitively impaired patients through the color choice preference in a group of Alzheimer’s disease (AD) patients and compare it with a group of Mild Cognitive Impairment (MCI) patients and a matched control group. Methods A total of 71 AD, 50 MCI and 68 controls were consecutively evaluated. All patients and controls underwent the Mini Mental State Evaluation (MMSE) and the Lüscher color test. Results Cognitively impaired patients mainly chose auxiliary colors, in particular violet and brown, and rejected black and gray. AD patients predominantly chose forms corresponding to auxiliary colors. The auxiliary color choice negatively correlated with the MMSE score. MCI patients and controls had a higher presence of anxiety on gray table and controls had higher frustration and ambivalence, i.e., psychic complexity, on basic color tables.Data globally suggest that AD patients live with a feeling of personal change due to instability and emotional insecurity, experiencing physical discomfort and a bodily need of being welcomed in a favorable environment. They aspire to a sensitive understanding by someone with whom they can be identified. Differently, MCI patients have less of these needs; however, they feel more anxious. Conclusion The comprehension of the inner emotional state of cognitively impaired patients allows us to better communicate with them and effectively approach their behavioral disorders. Like other projective techniques, such as the tree-drawing test and the human figure-drawing test, Lüscher color test is proposed as a simple and unconventional approach to understand the emotional life of AD patients. The awareness of clinicians about the existential fragility and insecurity of such type of patients allows us not only to better manage their behavioral disturbances but also to improve their quality of life and that of their caregivers.